War in the Villages : The U.S. Marine Combined Action Platoons in the Vietnam War - Easterling, Ted N., 1946- (Book collections on Project MUSE., 2021)
"Book describes and analyzes the Combined Action Platoons used by the U.S. Marine Corps from about 1965 to 1970 in the Vietnam War. These platoons contained U.S. Marines and Vietnamese popular forces and were embedded in smaller villages in South Vietnam in an effort to pacify the citizens and prevent the North Vietnamese from infiltrating the villages. Book analyzes their effectiveness as counterinsurgency forces"--